Lebanon : Staff Report for the 2015 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2015)
The Syrian crisis and the associated inflow of refugees continue to dominate Lebanon's short-term outlook, compounding long-standing policy weaknesses and vulnerabilities. Political paralysis has set in, with virtually no progress on the structural front. Growth has remained modest and insufficient to make a dent in rising poverty and unemployment. A welcome improvement in the primary fiscal position in 2014 was largely due to temporary factors, and will not be sustained absent adjustment efforts-implying that, without additional effort, Lebanon's already-sizable public debt burden will only worsen. Financial conditions have nonetheless remained stable, as deposit inflows continue to fund the economy and sizeable buffers support the credibility of the exchange rate peg.